Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Dan Sikap Remaja Tentang Bahaya Merokok - Zuhratul Hajri; Zurriyatun Thoyibah; Haryani Haryani (JURNAL KESEHATAN PRIMER, 2022)
Introductions: Indonesia takes first place among ASEAN countries with the highest rates of smokers in the world (50.68%). The number of smokers in NTB Province is increasing every year which is dominated by boys aged 15-18 years (58.4%). Smoking habits in adolescents is caused of lack of knowledge, advertising effect, and friends habit. Smoking behavior is close related to persons knowledge and attitude towards cigarettes. This research aims to determine the effect of health education toward knowledge and attitude of adolescent about smoking risk in SMK Islam Sirajul Huda Paok Dandak Janapria Central Lombok. Methods: The design of this research is pre-experimental using one-group pretest-posttest without a control group design. The sampling technique istotal sampling with number of respondents around 38 (male) students. The instrument of data collection is questionnaire.Result: The result of statistical test analysis using Wilcoxon obtained that P value=0.000 (<0.05), it is indicate that there is the effect of health education toward knowledge and attitude of adolescent about the risk of smoking in SMK Islam Sirajul Huda Paok Dandak Central Lombok. Conclusion: So it can be concluded that adolescent knowledge increases about the dangers of smoking after being given health education.  Keywords: Dangers of smokin; health education; youth